PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - , M. Arifuddin; , Dr. Sony Warsono, MAFIS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, the rising social and environmental awareness has directed an attitude change from profit orientation to social orientation in companies. Management as agents cannot escape the fact that companies' activities do not only affect the increase of profits and stock prices but also give social and environmental impacts such as ecosystem damage, pollutions, and social illness like discrimination and criminality which all falls under companies' social responsibility. This research aims to examine and observe the influence of corporate governance in gthe form of management ownership and institutional ownership portions in the company's stock, commissioner board measure, profitability, leverage, and company measure on the social and environmental disclosure in companies' annual report in Indonesia. The disclosure items include: environmental, energy, workforce health and safety issues, other human resources issues, products, and communities and public involvement. Sample size is 80 companies from 397 companies listed in the Jakarta Stock Exchange year 2009. Data analysis method used is multiple regression analysis with hypothesis testing through t-test and F-test. The result of this research states that management ownership, institution ownership, commissiones board measure, profitability, leverage, and company measure simultaneously influence the disclosure of corporate social responsibility with an R2 value of 52.5%. Thus, there are still 42.7% of other factors outside the independent variables researched that influence the disclosure of companies' CSR. the research result also state that: (i) management ownership negatively influences companies' CSR